The evolution of birth-order-specific son preference and compulsory primary education: Evidence from Vietnam - Ryo Hasegawa (PLoS ONE, 2025)
This paper examines birth-order-specific son preference and the effect of compulsory primary education on the male-skewed preference. Using four waves of Vietnamese decennial censuses from 1989 to 2019, the study finds that a desire to have a son at the first birth order—referred to as son-starting behavior—has emerged over time, particularly among small families. Exploiting a disproportionate increase in education in ethnic minorities triggered by the compulsory primary education law in 1991, difference-in-differences estimates suggest that female primary education reduces son-starting behavior by 3.13 percentage points. While this does not fully lead to gender neutrality across all birth orders, the magnitude is economically meaningful to mitigate the skewed preference for the first-born child. Mechanism analysis suggests that the effects could be mediated through an increased likelihood of marrying more educated husbands.